Hexacyanoferrate-based nanocomposites for the electrochemical sensing of hydrogen peroxide and nicotine / Lee Pui Kee - Lee , Pui Kee (2020)
Metal hexacyanoferrate (MeHCF) is a unique material that not only acquired immense research interest in electrochemical sensing field but also possesses potential as energy storage material. As such, the present thesis sought to investigate the facile method to synthesis MeHCF-based nanocomposites and explore its possible applications. First, comparative research on the synthesis of Prussian blue-polypyrrole (PB-PPy) nanocomposite by novel self-assembly (SA) method and conventional electrodeposition technique was performed. PB-PPy nanocomposites were prepared by the novel self-assembly method and via the electrodeposition approach. The nanocomposites were compared in term of surface morphology and its electrochemical and electrocatalytic characteristics. The results indicated that the SA PB-PPy with 10 deposition cycles demonstrated good sensing behaviour towards hydrogen peroxide (H2O2) with a sensitivity of 384.7 mA M-1 cm-2 whereas capacitive property was observed when the deposition cycles were increased to 20. The SA approach offers easy preparation of electrodes, which allows control of its electrochemical behaviour and sensitivity towards H2O2. The second part of this work emphasised on the facile synthesis of PB analogue: copper hexacyanoferrate (CuHCF) towards nicotine. Reduced graphene oxide (rGO) was used as a substrate to enhance operational stability. The linear range of this fabricated electrochemical sensor was between 0.03 to 5 mM, which is the highest among the reported works, with a compatible sensitivity of 211.5 mA M-1 cm-2. In addition, this sensor was applied for the detection of nicotine in vape (e-cigarette) sample from the market. For the last section of this work, the capacitive behaviour of SA PB-PPy by 20 deposition cycles was investigated as capacitor material. The areal capacitance of PB- PPy was at least ten-fold of pristine PB. This revealed PB-PPy can be a promising candidate for energy storage purpose.